2022
DOI: 10.3390/ijerph19116870
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Agents versus Ethylene Diamine Tetra Acetic Acid on Removal of the Smear Layer—A Systematic Review of In Vitro Studies

Abstract: This systematic review aimed to compare the efficacy of herbal agents with ethylene diamine tetraacetic acid (EDTA) in removing the smear layer during root canal instrumentation. The research question in the present study was to assess: “Is there a significant difference in reducing smear layer comparing EDTA and herbal agents?” Electronic databases (PubMed, Scopus, and Web of Science) were searched from their start dates to April 2022 using strict inclusion and exclusion criteria, and reviewed following PRISM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The observations indicate the better clearing efficacy of EDTA in smear layer removal than the other irrigants. Recent research has also suggested that EDTA outperforms herbal medicines in eliminating smear layers, which is in concordance with our findings [ 21 , 22 ]. Although it is vital in eliminating the smear layer, EDTA tends to cause dentinal erosion and increases the risk of perforation during instrumentation, depending on the concentration volume and contact time [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The observations indicate the better clearing efficacy of EDTA in smear layer removal than the other irrigants. Recent research has also suggested that EDTA outperforms herbal medicines in eliminating smear layers, which is in concordance with our findings [ 21 , 22 ]. Although it is vital in eliminating the smear layer, EDTA tends to cause dentinal erosion and increases the risk of perforation during instrumentation, depending on the concentration volume and contact time [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, existing literature supports the therapeutic benefits of combining glass ionomers with antimicrobial agents such as chlorhexidine and antibiotics. Nevertheless, this combination often leads to a compromise in the material’s strength properties [ 18 ]. Azadirachta indica , commonly known as neem, and Cymbopogon citratus , commonly known as lemongrass, are acknowledged for their multifaceted qualities.…”
Section: Discussionmentioning
confidence: 99%
“…Certain microorganisms are resistant to the cleaning and shaping processes and can continue to thrive within anatomical intricacies, which presents a challenge for clinical management ( Chueh and Huang, 2006 ). Persistent periapical lesions often contain Enterococcus faecalis because of the bacterium's propensity to colonize in dentinal tubules at varying depths ( Teja et al, 2022 ). Effective antimicrobial treatments are necessary for a defined period to ensure the cumulative elimination of root canal bacteria ( Banchs and Trope, 2004 ).…”
Section: Introductionmentioning
confidence: 99%